Foraging behavior interactions between two non-native social wasps, Vespula germanica and V. vulgaris: implications for invasion success? - Pereira, Ana Julia (2016)
Vespula vulgaris is an invasive scavenging social wasp that has very recently arrived in Patagonia (Argentina), a territory previously invaded -35 years earlier- by another wasp, V. germanica. Although V. vulgaris wasps possess features that could be instrumental in overcoming obstacles through several invasion stages, the presence of pre-established populations of V. germanica could affect their success. We studied the potential role played by V. germanica on the subsequent invasion process of V. vulgaris wasps in Patagonia by focusing on the foraging interaction between both species. This is because food searching and exploitation are likely to overlap strongly among Vespula wasps. We carried out choice tests where two types of baits were presented in a pairwise manner. We found experimental evidence supporting the hypothesis that V. germanica and V. vulgaris have asymmetrical response to baits with stimuli simulating the presences of each other. V. germanica avoided baits with either visual or actory cues indicating the V. vulgaris presence. However, V. vulgaris showed no preference between baits with or lacking V. germanica stimuli. These results suggest that the presence of an established population of V. germanica may not contribute to added biotic resistance to V. vulgaris invasion.